2020
DOI: 10.1007/s41230-020-9092-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on primary carbides precipitation in H13 tool steel regarding cooling rate during solidification

Abstract: This study aims to investigate the primary carbides precipitation in H13 steel solidified at relatively high cooling rates, ranging from 300 to 6,000 °C•min -1 , based on in situ observations with a high temperature confocal laser scanning microscope. In the cooling rate range investigated, the solidification microstructure becomes more refined as cooling rate increases and the relationship between the secondary dendrite arm spacing (SDAS), λ 2 , and cooling rate, .T, can be expressed as λ 2 =128.45.. Regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[1,2] However, the high-carbon and high-chromium contents of D2 cold-work die steel promote the formation of excessive amounts of M 7 C 3 carbides during solidification. [3,4] Large quantities and phases of carbides, such as networks formed by strip and herringbone M 7 C 3 carbides along dendrite boundaries, are difficult to eliminate in subsequent processing. This drawback makes D2 cold-work die steel susceptible to crack formation under external forces, which causes early cracking of the material in service.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] However, the high-carbon and high-chromium contents of D2 cold-work die steel promote the formation of excessive amounts of M 7 C 3 carbides during solidification. [3,4] Large quantities and phases of carbides, such as networks formed by strip and herringbone M 7 C 3 carbides along dendrite boundaries, are difficult to eliminate in subsequent processing. This drawback makes D2 cold-work die steel susceptible to crack formation under external forces, which causes early cracking of the material in service.…”
Section: Introductionmentioning
confidence: 99%
“…The linear intercept method was used to measure SDAS in the optical images. [12,24] To ensure the reliability of the measured SDAS results, five micrographs were selected and at least ten lines were drawn in one micrograph. The cooling rates can be estimated from the SDAS of the continuous casting billet specimens on the basis of the following equation: [22]…”
Section: A Identification Of the Sdasmentioning
confidence: 99%
“…With these drawbacks, the continuous casting billet could hardly achieve the best mechanical properties, leading to degrading of the finished product. [12][13][14][15] According to Han's [16] research, in some cases of excessive secondary cooling intensity condition, the temperature around the billet corner was around 500 °C, when it was out of the secondary cooling zone, while the temperature of the center surface was > 900 °C. The temperature difference between the billet corner and center surface after secondary cooling exceeded 400 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Loria [ 11 ] also found the faster cooling has refined solidification microstructure, but it did not change the type of carbides. With the high‐temperature confocal laser scanning microscope (HT‐CLSM) applied, Zang et al [ 12 ] indicated that the primary carbide is obviously reduced and the microstructure is refined with a higher cooling rate. As the primary carbide cannot be eliminated in the solidification process, Li et al [ 13 ] investigated the carbide resolution in the heat treatment and found the diameter of undissolved carbides increase with the austenitizing time, which indicates the carbide dissolution and coarsening occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, the alloy addition [ 6–8 ] and solidification rate [ 9–12 ] on the microstructure and carbide precipitation are studied, and the carbide resolution in heat treatment [ 13–15 ] are also investigated. It is commonly known that the cooling rate can affect the solidification behavior, while the temperature interval on the microstructure and primary carbide precipitation was rarely reported.…”
Section: Introductionmentioning
confidence: 99%